PLACE, MEMORY, AND LANGUAGE: VERNACULAR TOPONYMS AS COGNITIVE ANCHORS IN GLOBAL COMMUNICATION - Davletova, Saltanat E.; Bizhkenova, Aigul Y.; A.Burkova, Tatiana (Proceeding International Symposium on Global Education, Psychology, and Cultural Synergy, 2025)
This study explores the role of vernacular toponyms as cognitive and communicative anchors in globalized linguistic environments. The research addresses how local place names, often neglected in formal cartography, preserve cultural memory and linguistic identity while facilitating cross-cultural understanding. Using a mixed qualitative–cognitive approach, the study analyzes English and Kazakh vernacular toponyms collected from online discourse, local narratives, and digital maps. The findings reveal that vernacular toponyms function not merely as spatial markers but as carriers of embodied memory, emotion, and identity. They provide insight into how communities linguistically negotiate belonging in a globalized context. The study concludes that preserving vernacular place names strengthens linguistic diversity and fosters intercultural dialogue in global communication.